Effect of Seed Size and Kombucha Soaking on Soursop Germination and Seedling Growth - Wardah Naila Rahmatika; Florentina Kusmiyati; Syaiful Anwar (Jurnal Ilmu Pertanian Indonesia, 2026)
The purpose of this study was to look into the influence of long-term soaking seeds in kombucha and seed sizes on seed viability and seedling growth of soursop. The experiment was place between March and July 2024 at Screenhouse and the Undip Plant Physiology and Breeding Laboratory. The experiment followed a completely randomized factorial design with three replications. The first factor was the duration of seeds soak in kombucha (quick dipping, 2 h, 4 h, and 6 h). The second factor was varying seed sizes according on diameter. Seeds from local fruit varieties were removed, picked, and steeped in kombucha according to treatment, before being planted in a germination box and put into polybags for seedling growth. Germination time, vigor index, germinability,germinating speed, sprout wet and dry weight, seedling height, number of leaves, stem diameter, and seedling wet and dry weight were the parameters measured. The data were analyzed using ANOVA, with an honest significance difference at the 5% level. The results showed an interaction between the treatment and sprout dry weight parameter. Soaking seeds in kombucha with a quick dipping approach influenced germination speed and number of leaves; soaking seeds in kombucha for 4 h produced the maximum sprout dryweight. Different seed size had a substantial influence, with large seeds showing the greatest values for sprout wet and dry weight and stem diameter. Large seeds steeped in kombucha for 4 h produced the highest viability and growth of soursop seedlings. Keywords: kombucha, seedsize, seed soaking time, seedling, soursop